Respuesta :
Answer:
The expression [tex]-(\frac{1y}{2}+\frac{1}{4} )[/tex] is equivalent to the expression [tex]\frac{-1}{4}+\frac{-1y}{2}[/tex] .
Option (A) is correct .
Step-by-step explanation:
As given the expression in the question be as follow .
[tex]= -(\frac{1y}{2}+\frac{1}{4} )[/tex]
it is also written as
[tex]= -\frac{1y}{2}-\frac{1}{4}[/tex]
Now take
[tex]= \frac{-1}{4}(1+2y)[/tex]
Simplify the expression
[tex]= \frac{-1}{4}+2y\times \frac{-1}{4}[/tex]
[tex]= \frac{-1}{4}+\frac{-2y}{4}[/tex]
[tex]= \frac{-1}{4}+\frac{-1y}{2}[/tex]
Therefore the expression [tex]-(\frac{1y}{2}+\frac{1}{4} )[/tex] is equivalent to the expression [tex]\frac{-1}{4}+\frac{-1y}{2}[/tex] .
Option (A) is correct .